The Roehampton Campus Project: Using campus, collections and memories of the university as a learning and teaching resource for Humanities students. (October 2019) - Behr, Charlotte; Nevin, Sonya
In this article, we present a newly developed undergraduate module that is taught in the Humanities Department of the University of Roehampton. Campus and university themselves are the topics of the module. The module provides an opportunity for the students to engage academically with their environment. They study not only many interesting stories related to the campus, its buildings and artworks and the history(ies) of the university and its constituent colleges, they also explore their historical contexts. They have the rare chance to engage with original artefacts and archival materials directly unmediated by editorial and scholarly work. For their assignments, the students conduct research projects that are based on the resources of campus and university. They are required to present the results of their research in a public forum to provide them, early in their university studies, with experience of public engagement.